The challenge of outsourcing of hospital services in Iran: A qualitative study - Noureddin Niknam; Hasan Abolghasem Gorji; Mostafa Langarizadeh (Wolters Kluwer Medknow Publications, 2020)
INTRODUCTION: Outsourcing, as one of the important managerial strategies to improve performance, has become one of the main areas of research in hospital management studies. The aim of this study was to identify the challenges of outsourcing hospital services in Iran. METHODS: This research was conducted in a qualitative manner with the aim of determining the challenges of outsourcing hospital services in Iran. The research community consisted of managers and experts in the field of outsourcing. 21 managers and staff experts of the Ministry of Health, universities, and hospitals affiliated to Iran University of Medical Sciences, Tehran, and Shahid Beheshti, were selected as the target for the interview. Finally, the data were analyzed using content analysis method. RESULTS: Outsourcing challenges were extracted and reported in the form of 6 theme topics and 40 subthemes. The main issues included legal and political challenges, finance, human resources, organizational, managerial, and private sector. CONCLUSION: Outsourcing hospital services in all six areas faced serious challenges. To this end, partnership between the private and government sectors through outsourcing requires the continuous development of effective political, organizational, and managerial capacity in order to guide and manage this process properly and efficiently to ensure that the goals and policies in the field of health. It is clearly understood and not forgotten or neglected.